1976
DOI: 10.1042/bj1560103
|View full text |Cite
|
Sign up to set email alerts
|

Lipid composition of lymphocyte plasma membrane from pig mesenteric lymph node

Abstract: 1. The lipid fraction of the plasma membrane of pig mesenteric lymph-node lymphocytes contained primarily (94%) neutral lipids and phospholipids in about equal weights. The remianing lipid comprised glycosphingolipids (1.8%), gangliosides (o.27%)and probably ceramides (1.3%). The major phospholipid was phosphatidylcholine (46% of the total), and mono- and tri-hexosylceramides accounted for 72% of the glycosphingolipids. Haematoside was distributed between the glycosphingolipid and ganglioside fractions. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Gangliosides (SP0601) constitute a subgroup of acidic glycosphingolipids (SP06) with one or more terminal sialic acids. The total ganglioside content of the plasma membrane (PM) can reach up to 1% -2%, with individual gangliosides in the range of 0.01% -0.1% (Levis et al 1976;Ortegren et al 2004;Sonnino et al 2006). The glycosphingolipids are enriched in the apical domain of polarized cells (Crespo et al 2008), and they are especially abundant in neurons (Sonnino et al 2006).…”
Section: Glycosphingolipidsmentioning
confidence: 99%
“…Gangliosides (SP0601) constitute a subgroup of acidic glycosphingolipids (SP06) with one or more terminal sialic acids. The total ganglioside content of the plasma membrane (PM) can reach up to 1% -2%, with individual gangliosides in the range of 0.01% -0.1% (Levis et al 1976;Ortegren et al 2004;Sonnino et al 2006). The glycosphingolipids are enriched in the apical domain of polarized cells (Crespo et al 2008), and they are especially abundant in neurons (Sonnino et al 2006).…”
Section: Glycosphingolipidsmentioning
confidence: 99%
“…Only traces of this small ganglioside are found in normal human lymphocytes, but the lymphoblastoid cells BRI-8 contain considerable amounts, primarily concentrated in their plasma membranes, where a 10-fold increase enrichment has been found [6]. Plasma membranes from pig mesenteric lymph nodes are also enriched in gangliosides [13].…”
Section: Discussionmentioning
confidence: 88%
“…Only traces of this small ganglioside are found in normal human lymphocytes, but the lymphoblastoid cells BRI-8 contain considerable amounts, primarily concentrated in their plasma membranes, where a 10-fold increase enrichment has been found [6]. Plasma membranes from pig mesenteric lymph nodes are also enriched in gangliosides [13]. Since lymphocytes are transformed to lymphoblasts after stimulation with lectins, it might tie suggested that an active biosynthesis of II'NeuAc-LacCer by these cells, in accordance with evidence mentioned above, is needed to satisfy requirements for new membrane formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations